2018
DOI: 10.2106/jbjs.17.00892
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Five-Year Outcomes of Hip Arthroscopy for the Treatment of Femoroacetabular Impingement and Labral Tears in Patients with Obesity

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
3
47
2
Order By: Relevance
“…Although obese patients demonstrate improvement after arthroscopy, studies indicate that the obese population is more likely to require a subsequent revision arthroscopy or THA. 21,36 In a matched controlled study, Gupta et al 21 noted that obese patients, defined as having a BMI >30, demonstrated significantly lower patient-reported outcomes at 2 years postoperatively and were twice as likely to convert to a revision hip arthroscopy or THA when compared with nonobese patients. Furthermore, our results indicating that patients with a greater BMI are more likely to convert to THA are consistent with existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although obese patients demonstrate improvement after arthroscopy, studies indicate that the obese population is more likely to require a subsequent revision arthroscopy or THA. 21,36 In a matched controlled study, Gupta et al 21 noted that obese patients, defined as having a BMI >30, demonstrated significantly lower patient-reported outcomes at 2 years postoperatively and were twice as likely to convert to a revision hip arthroscopy or THA when compared with nonobese patients. Furthermore, our results indicating that patients with a greater BMI are more likely to convert to THA are consistent with existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results indicating that patients with a greater BMI are more likely to convert to THA are consistent with existing literature. 36…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Yet, as with all orthopaedic procedures, rate of recovery and outcomes are highly influenced by patient-specific factors, including age, sex, body habitus, and arthritic changes. 10,11 Increasing evidence has demonstrated that outcomes of orthopaedic procedures also depend on patient psychological traits, which can affect compliance, rehabilitation effort, and pain perception. 12,13 It recently has been shown that psychological factors such as depression and distress are predictors of lower preoperative patient-reported outcome scores, chronic postoperative pain, and poor outcomes following hip arthroscopy.…”
mentioning
confidence: 99%
“…The anterolateral (AL) portal is usually the very first access portal created when performing hip arthroscopy. Anatomically, it has been standardized relative to the location of the greater trochanter (GT) 1, 2, 3, 4…”
mentioning
confidence: 99%